2021
DOI: 10.3389/fspas.2021.735034
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Structure in the Solar Wind

Abstract: Structures in the solar wind result from two basic mechanisms: structures injected or imposed directly by the Sun, and structures formed through processing en route as the solar wind advects outward and fills the heliosphere. On the largest scales, solar structures directly impose heliospheric structures, such as coronal holes imposing high speed streams of solar wind. Transient solar processes can inject large-scale structure directly into the heliosphere as well, such as coronal mass ejections. At the smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 232 publications
0
24
0
Order By: Relevance
“…Decades of in situ observations have revealed that the solar wind is not laminar, but rather highly structured at many different scales (Verscharen et al 2019;Viall et al 2021). On mesoscales, scales that are smaller than the largest structures in the solar wind but larger than kinetic scales, some structures enter the solar wind directly from the solar atmosphere during their formation while others evolve during propagation.…”
Section: Mesoscale Periodic Structures In the Solar Windmentioning
confidence: 99%
See 1 more Smart Citation
“…Decades of in situ observations have revealed that the solar wind is not laminar, but rather highly structured at many different scales (Verscharen et al 2019;Viall et al 2021). On mesoscales, scales that are smaller than the largest structures in the solar wind but larger than kinetic scales, some structures enter the solar wind directly from the solar atmosphere during their formation while others evolve during propagation.…”
Section: Mesoscale Periodic Structures In the Solar Windmentioning
confidence: 99%
“…Mesoscale structures in the solar wind not only provide information about the formation of the solar wind in general, but are also important because they can drive the dynamics of magnetospheres (Di Matteo et al 2022) and they form the medium through which larger space weather events propagate. Viall et al (2021) provide a comprehensive review of mesoscales, including periodic density structures, observed throughout the heliosphere. They have been observed at scales as small as several minutes (or ~100 Mm) and as large as several hours (or several thousand megameters).…”
Section: Mesoscale Periodic Structures In the Solar Windmentioning
confidence: 99%
“…Structures in the solar wind can be either injected remnants of solar corona processes or locally generated in situ by dynamical process en route to the observation point (Borovsky, 2021 ; Viall et al., 2021 ). Many statistical and case studies have shown that the solar wind at 1 AU contains periodic proton density structures at length scales that occur more often than others (Kepko et al., 2020 , and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Using the OMNI dataset we cannot completely remove the effect of latitudinal offset, θ (see also Turner et al, 2021) or transients resulting from either unidentified ICMEs and/or turbulent and mesoscale structures (Viall, DeForest, and Kepko, 2021;Verscharen, Klein, and Maruca, 2019). Thus, it is useful to also examine simulation results that attempt to capture only the ambient solar wind.…”
Section: In Situ Spacecraft Observationsmentioning
confidence: 99%